2018
DOI: 10.1155/2018/5246516
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological Spectrum of Thyroiditis: A Review of 110 Cases

Abstract: Introduction Different types of thyroiditis may share some parallel clinical and biochemical features. Timely intervention can significantly reduce morbidity and mortality. Aim Aim of this study is to find the frequency of various thyroiditis, study the cytomorphological features and correlate with clinical findings including radiological findings, thyroid function test, and anti-thyroid peroxidase antibodies (Anti-TPO antibodies). Materials and Methods The study included consecutive 110 cases of thyroiditis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
2
19
2
Order By: Relevance
“…The peak age incidence of HT in our study was the third to fourth decade of life, which is in accordance with other Indian studies unlike the Western literature (fifth decade of life). [2910] Female predominance was seen in our study with a female: male ratio of 14.7:1, similar to other studies. Diffusely enlarged thyroid is the most common presentation of this form of thyroiditis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The peak age incidence of HT in our study was the third to fourth decade of life, which is in accordance with other Indian studies unlike the Western literature (fifth decade of life). [2910] Female predominance was seen in our study with a female: male ratio of 14.7:1, similar to other studies. Diffusely enlarged thyroid is the most common presentation of this form of thyroiditis.…”
Section: Discussionsupporting
confidence: 90%
“…Hormonal assays done in our study showed a majority (74%) of the patients to be hypothyroid in agreement with previous studies. [21011] The state where T3 and T4 are normal with TSH being above the defined upper limit of the reference range is called subclinical hypothyroidism, representing an early phase of hormonal imbalance. In this study, 39.6% of the cases presented with SCH, similar to a study of Bhatia et al [2].…”
Section: Discussionmentioning
confidence: 99%
“…On assessing thyroid hormonal status, majority of the patients were hypothyroid similar to many other studies. 8,12,14 Patients with subclinical hypothyroidism in our study were 11 (14.10%). In a study by Shetty et al, 12 39.6% of the cases presented with subclinical hypothyroidism which is higher than our study.…”
Section: Discussionmentioning
confidence: 58%
“…In thyroiditis de Quervain, histiocytes, plasma cells and T lymphocytes dominate the active phase (13). Cytomorphical features of fine needle aspiration include many giant cells, which are considered histiocytes (14). Immune cells in the specimen of our patient consisted mostly of CD3+ T lymphocytes (predominantly CD4+ helper T-cells, about 10% CD8+ suppressor T-cells), while plasma T cells were only sparsely observed.…”
Section: Discussionmentioning
confidence: 59%